NONFORMAL EDUCATION AS A STRATEGIC APPROACH TO REDUCING EDUCATIONAL INEQUALITY: EXPANDING LEARNING ACCESS BEYOND FORMAL SCHOOLING - Helmi; Rila Hardiansyah (Adisam Publisher, 2026)
Educational inequality remains a persistent challenge in many developing countries, particularly among marginalized communities with limited access to formal schooling. Nonformal education, often implemented through community-based and lifelong learning programs, offers flexible and inclusive learning opportunities for individuals excluded from formal education systems. This study aims to analyze the role of nonformal education as a strategic mechanism for reducing educational disparities and promoting social inclusion. Using a qualitative literature review approach, this study synthesizes findings from previous research, policy documents, and reports related to nonformal education initiatives. The analysis indicates that nonformal education contributes significantly to expanding educational access, improving life skills, and enhancing community empowerment, especially among disadvantaged populations. However, challenges remain in program sustainability, policy integration, and quality assurance. Strengthening collaboration among governments, communities, and educational institutions is essential to maximize the impact of nonformal education programs. The study highlights the importance of positioning nonformal education as a complementary pathway within national education systems to achieve equitable and inclusive lifelong learning.